Protein disulfide isomerase family member 4 promotes triple-negative breast cancer tumorigenesis and radiotherapy resistance through JNK pathway - Jinqiu Tao; Cailin Xue; Meng Cao; Jiahui Ye; Yulu Sun; Hao Chen; Yinan Guan; Wenjie Zhang; Weijie Zhang; Yongzhong Yao (Breast Cancer Research, 2024)
Abstract Background Despite radiotherapy ability to significantly improve treatment outcomes and survival in triple-negative breast cancer (TNBC) patients, acquired resistance to radiotherapy poses a serious clinical challenge. Protein disulfide isomerase exists in endoplasmic reticulum and plays an important role in promoting protein folding and post-translational modification. However, little is known about the role of protein disulfide isomerase family member 4 (PDIA4) in TNBC, especially in the context of radiotherapy resistance. Methods We detected the presence of PDIA4 in TNBC tissues and paracancerous tissues, then examined the proliferation and apoptosis of TNBC cells with/without radiotherapy. As part of the validation process, xenograft tumor mouse model was used. Mass spectrometry and western blot analysis were used to identify PDIA4-mediated molecular signaling pathway. Results Based on paired clinical specimens of TNBC patients, we found that PDIA4 expression was significantly higher in tumor tissues compared to adjacent normal tissues. In vitro, PDIA4 knockdown not only increased apoptosis of tumor cells with/without radiotherapy, but also decreased the ability of proliferation. In contrast, overexpression of PDIA4 induced the opposite effects on apoptosis and proliferation. According to Co-IP/MS results, PDIA4 prevented Tax1 binding protein 1 (TAX1BP1) degradation by binding to TAX1BP1, which inhibited c-Jun N-terminal kinase (JNK) activation. Moreover, PDIA4 knockdown suppressed tumor growth xenograft model in vivo, which was accompanied by an increase in apoptosis and promoted tumor growth inhibition after radiotherapy. Conclusions The results of this study indicate that PDIA4 is an oncoprotein that promotes TNBC progression, and targeted therapy may represent a new and effective anti-tumor strategy, especially for patients with radiotherapy resistance.